2011
DOI: 10.1074/jbc.m111.222430
|View full text |Cite
|
Sign up to set email alerts
|

Role of Matrix Metalloproteinase 3-mediated α-Synuclein Cleavage in Dopaminergic Cell Death

Abstract: Evidence suggests that the C-terminal truncation of ␣-synuclein is equally important as aggregation of ␣-synuclein in Parkinson disease (PD). Our previous results showed that an endopeptidase, matrix metalloproteinase-3 (MMP3), was induced and activated in dopaminergic (DA) cells upon stress conditions. Here, we report that MMP3 cleaved ␣-synuclein in vitro and in vivo and that ␣-synuclein and MMP3 were co-localized in Lewy bodies (LB) in the postmortem brains of PD patients. Incubation of ␣-synuclein with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
98
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(100 citation statements)
references
References 43 publications
1
98
0
1
Order By: Relevance
“…In this regard, we have previously shown a region-dependent alteration/expression of MMPs in the putamen and cortex of MSA patients (55). MMPs have been previously shown to cleave α-syn, thereby producing truncated forms (52,54). We here present an in vivo proof of concept of the ability of the caspase-1 inhibitor prodrug VX-765 to mitigate α-syn pathology and to mediate neuroprotection in an MSA mouse model.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…In this regard, we have previously shown a region-dependent alteration/expression of MMPs in the putamen and cortex of MSA patients (55). MMPs have been previously shown to cleave α-syn, thereby producing truncated forms (52,54). We here present an in vivo proof of concept of the ability of the caspase-1 inhibitor prodrug VX-765 to mitigate α-syn pathology and to mediate neuroprotection in an MSA mouse model.…”
Section: Discussionmentioning
confidence: 66%
“…Some studies have shown that C-terminally truncated α-syn is found in GCIs in MSA (48,49) as well as in Lewy bodies of PD and DLB patient brains (11,12,39,50,51). Several proteases such as calpain, matrix metalloproteases (MMPs), cathepsin D, and plasmin have been implicated in α-syn truncation, subsequently resulting in increased levels of protein aggregates; however, none has been established as a major producer of C-terminally truncated α-syn in vivo, especially in response to inflammation (12,39,42,(52)(53)(54)(55).…”
Section: Discussionmentioning
confidence: 99%
“…This has important consequences since MMP-3 cleaves a-synuclein in vitro and in vivo and a-synuclein and MMP-3 co-localize in Lewy bodies (LB), as observed in post-mortem brains of PD patients (Choi et al, 2011). Evidence from in vitro investigations suggests that the MMP-3 mediated C-terminal truncation of a-synuclein releases fragments with the tendency to aggregate.…”
Section: Diseases Of the Nervous Systemmentioning
confidence: 99%
“…Alternately, if a-syn were enclosed in an exocytosed vesicle 10,15 or exosome, 14,49 as described above, the protein would be protected during its journey from extracellular enzymes. If unprotected, the risk for degradation is apparent as matrix metalloproteinase 3 has been shown to cleave both recombinant a-syn proteins 56,57 and neuroblastoma cell-secreted a-syn. 56 Recently, it was suggested that the molecular chaperone heat shock protein 70 (Hsp70) is released from cells together with a-syn and might modulate levels of extracellular a-syn oligomers.…”
Section: Molecular Mechanisms Involved In Intercellular Transfer Of Amentioning
confidence: 99%